Model of Strengthening Halal Branding as an Implementation of Wellness Economy for MSMEs in Jember Regency - Adenan , Moh; Cholifah , Umi; Prasetiyaningtiyas , Susanti; Wulandari , Deasy; Subagio, N. Ari; Prianto, Fajar Wahyu (Future Science / FSH-PH Publications, 2023)
The new lifestyle of the people that emerged as a result of the Covid-19 Pandemic which emphasizes the importance of a healthy lifestyle also influences economic and social activities in implementing the wellness economy. Healthy food can be traced from raw materials, processes, finished products and physical presentation to hygiene and in the concept of sharia it is called halal food which legally has a halal certificate. The purpose of this study was to identify MSMEs that already have halal certificates, analyze challenges and opportunities, analyze the effect of halal branding on sales, and formulate a model for strengthening MSME halal branding in Jember Regency. The method used is the Mix Method, beginning with a qualitative descriptive with secondary data collection, observation, and Focus Group Discussion (FGD). The results obtained are about 8, There are 764 MSMEs in Jember Regency and only 5% are halal certified. The minimum number of MSMEs that have halal certificates is because there are obstacles such as a lack of understanding of registration procedures, too many registration requirements, small businesses, time constraints.